All in a Day's Work A look at The Bournonville School - Freeman, Frank (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Bournonville classes on DVD. PALABRAS CLAVE: Bournonville School.
Distributed outside Denmark by Dance Books. www.dancebook.co.uk